2012
DOI: 10.1177/0888406412444763
|View full text |Cite
|
Sign up to set email alerts
|

Market Demand for Special Education Faculty

Abstract: Since 1988, researchers have monitored the supply of and demand for special education (SE) faculty. The demand side of these studies was initiated by Sindelar and Taylor (1988), and the continued imbalance between the supply of new graduates and demand at the nation's SE teacher preparation programs is now well

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…It is not easy to select and employ successful educators and impactful researchers in academia; the recruitment of future faculty members is a challenge in all disciplines. In fact, a shortage of SPED faculty members has been reported in many countries (Montrosse & Young, 2012;Smith et al, 2010;West & Hardman, 2012). There is a growing demand for faculty members in SPED because of the need to replace retired faculty and due to the growing interest in the field in many developing countries (Ametepee & Anastasiou, 2015;Anastasiou & Keller, 2017).…”
Section: The Selection Of Potential Faculty Members For Spedmentioning
confidence: 99%
“…It is not easy to select and employ successful educators and impactful researchers in academia; the recruitment of future faculty members is a challenge in all disciplines. In fact, a shortage of SPED faculty members has been reported in many countries (Montrosse & Young, 2012;Smith et al, 2010;West & Hardman, 2012). There is a growing demand for faculty members in SPED because of the need to replace retired faculty and due to the growing interest in the field in many developing countries (Ametepee & Anastasiou, 2015;Anastasiou & Keller, 2017).…”
Section: The Selection Of Potential Faculty Members For Spedmentioning
confidence: 99%
“…As West and Hardman (2012) stated, "The 2001 study established an indisputable link between the shortage of special education faculty in universities and colleges and the pervasive shortage of special education teachers" (p. 155). Montrosse and Young (2012) suggested that "retirements across all special education programs (i.e., doctoral and teacher education combined) are predicted to increase by 21% per year between 2011 and 2017" (p. 149). Smith and Montrosse (2012) suggested that although the number of doctoral preparation programs graduating funded scholars increased between 2002 and 2012, the programs producing the graduates are projected to lose more than half of their faculty due to retirement in the next 5 years.…”
Section: Increasing Fundingmentioning
confidence: 99%
“…It is imperative that a sufficient supply of doctoral graduates be trained to replenish those faculty who are retiring (Smith et al, 2010). In addition, of the current graduates, only half enter academe (Smith montross, Robb Tyler and Young, 2011), calling into question the extent to which our current supply can meet the predicted demand (Montrosse & Young, 2012). Montrosse and Young (2012) suggested that "retirements across all special education programs (i.e., doctoral and teacher education combined) are predicted to increase by 21% per year between 2011 and 2017" (p. 149).…”
Section: Increasing Fundingmentioning
confidence: 99%
See 2 more Smart Citations